PENEGAKAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA PERJUDIAN MELALUI PENDEKATAN RESTORATIF JUSTICE (LAW ENFORCEMENT AGAINST CHILDREN AS PERPETRATORS OF CRIMINAL ACTS OF GAMBLING THROUGH THE RESTORATIVE JUSTICE APPROACH) - Aulia Aziza (2021)
Gambling often positions children to deal with the judicial process. The purpose of juvenile justice is to create a justice that guarantees the best interests of children, but then, juvenile justice in Indonesia has not been able to provide a sense of justice towards children, often resulting in children's rights being neglected. This research was conducted using a juridical normative. The focus of this research is that the formal judicial process by imposing criminal penalties for children is not the best solution in solving gambling cases committed by children, because basically children who commit acts of gambling are influenced by other factors, and also the criminalization of children has a negative impact on the child. So that the child justice process that applies in Indonesia is currently considered less effective in protecting the best interests of the child so that there is a need for efforts to resolve other cases that better guarantee the best interests for children, one of which is the settlement of child cases with a restorative justice approach through the diversion process.